The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1016/s0893-133x(98)00082-7
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Preferentially Increases Dopamine Release in the Rhesus Monkey Prefrontal Cortex Compared with the Caudate Nucleus

Abstract: Despite substantial differences between species in the organization and elaboration of the cortical dopamine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 32 publications
4
42
0
1
Order By: Relevance
“…Both clozapine and haloperidol, given acutely, increase extracellular levels of dopamine in the prefrontal cortex and striatal complex. Acute clozapine treatment preferentially increased prefrontal dopamine release in the rat; whereas, haloperidol preferentially increased striatal dopamine efflux (Moghaddam and Bunney 1990;Pehek et al 1993;Youngren et al 1994), and our group has recently observed a similar effect in the monkey (Youngren et al 1998). Thus, clozapine (at doses that do not potently block D 1 -like receptors) may actually potentiate transmission at this receptor subtype.…”
Section: Response Of Pcp Effects To Antipsychotic Drugsmentioning
confidence: 75%
“…Both clozapine and haloperidol, given acutely, increase extracellular levels of dopamine in the prefrontal cortex and striatal complex. Acute clozapine treatment preferentially increased prefrontal dopamine release in the rat; whereas, haloperidol preferentially increased striatal dopamine efflux (Moghaddam and Bunney 1990;Pehek et al 1993;Youngren et al 1994), and our group has recently observed a similar effect in the monkey (Youngren et al 1998). Thus, clozapine (at doses that do not potently block D 1 -like receptors) may actually potentiate transmission at this receptor subtype.…”
Section: Response Of Pcp Effects To Antipsychotic Drugsmentioning
confidence: 75%
“…The atypical and clinically superior antipsychotic drug, clozapine, has already been demonstrated to preferentially release DA in the prefrontal cortex of the rat (Moghaddam and Bunney 1990; Pehek and Yamamoto 1994;Yamamoto and Cooperman 1995) as well as of the non-human primate (Youngren et al 1999) and to preferentially activate DA neurons projecting to cortical regions (White and Wang 1983;Goldstein et al 1993). Accordingly, we postulated that the co-administration of tyrosine and clozapine would potentiate MPFC DA synthesis.…”
Section: Tyrosine Availability Can Influence Dopamine (Da) Synthesis mentioning
confidence: 89%
“…Intriguingly, in rats pretreated with FG-7142, a beta-carboline known to preferentially increase MPFC synthesis, utilization and release Roth 1985, 1990;Bradberry et al 1991), administration of tyrosine robustly enhances MPFC DA synthesis (Tam et al 1990). We postulated that such precursor dependence would also be established by other drugs which activate mesocortical dopaminergic activity.The atypical and clinically superior antipsychotic drug, clozapine, has already been demonstrated to preferentially release DA in the prefrontal cortex of the rat (Moghaddam and Bunney 1990; Pehek and Yamamoto 1994;Yamamoto and Cooperman 1995) as well as of the non-human primate (Youngren et al 1999) and to preferentially activate DA neurons projecting to cortical regions (White and Wang 1983;Goldstein et al 1993). Accordingly, we postulated that the co-administration of tyrosine and clozapine would potentiate MPFC DA synthesis.…”
mentioning
confidence: 89%
“…Several laboratories have shown that clozapine releases dopamine in frontal cortex in animal preparations, an action possibly related to its serotonin and/or noradrenergic receptor affinity (Pehek et al, 1994;Pehek, 1996;Rollema et al, 1997;Moghaddam and Bunney, 1999;Hertel et al, 1999;Youngren et al, 1999). In electrophysiologic and immediate-early gene studies, clozapine and other secondgeneration antipsychotics demonstrate limbic selectivity in that they preferentially affect dopamine neurons projecting to limbic areas (Chiodo and Bunney, 1983;White and Wang, 1983;Robertson and Fibiger, 1992).…”
Section: Discussionmentioning
confidence: 99%